Sistem Buka Tutup Pintu Otomatis dengan Sensor Ultrasonik - Mulyahani, Alvina; Ibrahim, Ibrahim; Saragih, Yuliarman Saragih (Peneliti.net, 2023)
Rapid improvements in electronic instrumentation technology have now become important for human life. Speed, accuracy, efficiency and effectiveness are important needs that can be addressed through automated systems. One example of implementing an efficient automatic system is the door opening and closing process. Components in this automatic system include Arduino Uno, ultrasonic sensors, servo motors, light emitting diodes and resistors. In testing the sensor works well, that is, the working system of this tool if it detects a person or object according to the predetermined sensor distance then the door will open, if it does not match the predetermined distance then the door will not open.